Energy Policy and Climate Crisis: an Evaluation of the Adequacy of Energy Laws in Supporting the Transition to Clean and Sustainable Energy - RAHMADINA, Adji Annisa (Indonesia Strategic Sustainability, 2024)
The climate crisis is becoming an increasingly urgent global challenge that profoundly impacts agriculture, ecosystems, and public health. According to the 2024 Intergovernmental Panel on Climate Change (IPCC) report, global temperatures have risen by 1.2°C since the pre-industrial era, and this warming is primarily driven by emissions from the energy sector, particularly the burning of fossil fuels. As one of the largest carbon-emitting countries, Indonesia remains heavily reliant on fossil fuels, especially coal, which accounts for around 60% of its electricity generation in 2024. Although Indonesia is endowed with significant renewable energy potential, various structural challenges, including ineffective policies and regulatory frameworks, hinder the solar, wind, and geothermal transition to clean Energy. The existing laws and regulations do not provide sufficient incentives for the development of renewable Energy, and bureaucratic hurdles, coordination issues among government agencies, and a lack of legal clarity on pricing and incentives further impede progress. This study aims to evaluate the adequacy of Indonesia's energy laws in supporting a clean and sustainable energy transition and to identify key legal barriers that need to be addressed. The findings are expected to contribute to policy recommendations that could strengthen Indonesia's legal framework, thus facilitating a more rapid and effective transition to a greener energy future.